2018
DOI: 10.2106/jbjs.17.01190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI Outcomes 10 Years After Repair of Massive Posterosuperior Rotator Cuff Tears

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
1
44
1
1
Order By: Relevance
“…Here the percentage of tendon healing was reported as ranging between 68% and 81%, depending on the initial type of tear, 2 and a separate study by the same study group on massive tears indicated a retear rate of 34%. 8 Interestingly, the differences in the retear rate between isolated SSp tears and larger tears with different extension were not found to be significant, although the failure rate was higher in the group with posterior extension. 2 This is in contrast to the results of the present study, where a significant difference in the proportion of intact RC was documented in C1-C2 tears versus C3-C4 (68% vs 29%, P = .0002).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Here the percentage of tendon healing was reported as ranging between 68% and 81%, depending on the initial type of tear, 2 and a separate study by the same study group on massive tears indicated a retear rate of 34%. 8 Interestingly, the differences in the retear rate between isolated SSp tears and larger tears with different extension were not found to be significant, although the failure rate was higher in the group with posterior extension. 2 This is in contrast to the results of the present study, where a significant difference in the proportion of intact RC was documented in C1-C2 tears versus C3-C4 (68% vs 29%, P = .0002).…”
Section: Discussionmentioning
confidence: 82%
“…The cohort presented in this study is the first one where ultrasound evaluation was performed to assess RC integrity after arthroscopic repair at a minimum follow-up of 10 years and the third one for which such long-term results are described. 2,8,15,21 Heuberer et al 21 presented in 2017 the results of a case series of 30 patients whose clinical outcomes were collected prospectively 10 years after arthroscopic RC repair with MRI assessment of RC integrity. More recently, several studies originating from the same cohort of patients, enrolled under the direction of the Société Française de Chirurgie Orthopédique et Traumatologique (SOFCOT) in 2003, were published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Good to excellent outcomes have been reported in the short- and long-term follow-up in most cases. 11,12,45,50 However, despite advances in instrumentation and surgical techniques, a risk of rerupture of 20% to 60% has been observed. 10,14 Although patients whose tendons fail to heal can still have pain relief, most studies have shown that patients with healed repairs achieve higher patient-reported outcome scores.…”
mentioning
confidence: 99%
“… 18 20 , 22 , 28 , 35 However, the retear rate in large/massive rotator cuff repair remains very high. 10 , 15 , 18 20 This could be ascribed to various factors such as poor tendon quality, high tension between tendon and suture, inferior fixation strength, and the slow healing process of the bone-tendon interface (BTI). 1 , 7 , 21 , 25 , 34 To reduce the retear rate and promote BTI healing, various biological and engineered patches have been developed, such as human acellular dermal allografts, 1 , 33 , 36 , 37 small intestinal submucosa, 8 , 12 , 14 , 30 and biodegradable synthetic polymers.…”
mentioning
confidence: 99%